"But now my eye sees you": Hierophany in Job and The Crying of Lot 49. (September 2016) - Carson, Jordan
This article argues Thomas Pynchon's The Crying of Lot 49 is a postsecular retelling of the book of Job. The novel not only alludes directly to Job, but shares plot, structure, and theme. Both texts explore religious meaning; divining the nature of the transcendent is the primary task of both protagonists. Further, both texts detail an education in uncertainty: as the voice from the whirlwind "answers" neither Oedipa nor Job according to expectations, each comes to understand the innate uncertainty of life and gains the self-knowledge and wisdom to live fully in spite of and according to this ambiguity.